Anxious Personality Traits: Perspectives from Basic Emotions and Neurotransmitters - Jie Dong; Tingwei Xiao; Qiuyue Xu; Fei Liang; Simeng Gu; Fushun Wang; Jason H. Huang (Brain Sciences, 2022)
Objective: Recently, many emotional diseases, such as anxiety and depression, have prevailed, and it is expected that emotional disease will be the leading cause of social and economic burden in 2030. These emotional diseases may be due to certain personality traits, which could be the reasons for the development of mental illness. Personality theories have been constantly developed over the past hundreds of years, and different dimensions of personality traits corresponding to different physiological bases and emotional feelings have been proposed. However, personality may be the least studied area in psychology. Methods: In this paper, we will give a short review on the development of personality theories as well as dimensional emotional theory. Then, we will compare the similarities between the emotional dimension and personality dimension. Furthermore, we will also investigate the neural mechanisms of personality and emotions, focusing on neuromodulators for anxiety-related personality traits, in order to provide a clear relationship between different neurotransmitters and anxiety-related personality traits. Results: The results of our study suggest that the emotional dimension and personality dimension may be somewhat related, for example, the extrovert/introvert dimension of personality might be related to the hedonic dimension, which includes happiness/sadness, and the neurotic dimensions might be related to emotional arousal. In addition, our study found that personality traits are also related to basic emotions, for instance, people who are too self-centered are prone to feeling a mood of disgust or depression, while anger and fear correspond to unstable personality traits. The analysis suggested that the neural substrates of both personality and emotions might be described as follows: extroverted–joy–dopamine (DA); introverted–disgust–5-hydroxytryptamine (5-HT); unstable (neuroticism)–anger/fear–noradrenaline (NE); stable–calmness. Conclusions: The results of this study suggest that there is a correlation between personality traits and emotions, and both depend on monoamine neurotransmitters (dopamine, norepinephrine and serotonin). In addition, personality disorders can be interfered via the regulation of emotions and neurotransmitters. This paper opens up a whole new perspective for future research on personality traits and emotional diseases and has great clinical value and practical significance.